2019
DOI: 10.1126/sciadv.aaw8072
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable hybrid perovskite light-emitting diodes based on Dion-Jacobson structure

Abstract: Organic-inorganic hybrid halide perovskites are emerging as promising materials for next-generation light-emitting diodes (LEDs). However, the poor stability of these materials has been the main obstacle challenging their application. Here, we performed first-principles calculations, revealing that the molecule dissociation energy of Dion-Jacobson (DJ) structure using 1,4-bis(aminomethyl)benzene molecules as bridging ligands is two times higher than the typical Ruddlesden-Popper (RP) structure based on phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
222
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(224 citation statements)
references
References 48 publications
(56 reference statements)
2
222
0
Order By: Relevance
“…[ 14 ] Y. Shang et al reported that the DJ‐phase structure would be beneficial to improve the device lifetime of LEDs, because the molecule dissociation energy of diammonium cation (i.e., 1,4‐bis(aminomethyl)benzene) in DJ‐type perovskites is higher than that of RP‐type perovskites containing phenylethylammonium ligands. [ 15 ] In addition, diammonium cation can be used as an additive in the perovskite ink formulation (MAPbI 3 ), which significantly improves efficiency and stability of perovskite solar cells. [ 16 ] More recently, Rashba effect and robust ferroelectricity have been observed in the DJ‐type perovskite of [4‐(aminomethyl)piperidinium]PbI 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Y. Shang et al reported that the DJ‐phase structure would be beneficial to improve the device lifetime of LEDs, because the molecule dissociation energy of diammonium cation (i.e., 1,4‐bis(aminomethyl)benzene) in DJ‐type perovskites is higher than that of RP‐type perovskites containing phenylethylammonium ligands. [ 15 ] In addition, diammonium cation can be used as an additive in the perovskite ink formulation (MAPbI 3 ), which significantly improves efficiency and stability of perovskite solar cells. [ 16 ] More recently, Rashba effect and robust ferroelectricity have been observed in the DJ‐type perovskite of [4‐(aminomethyl)piperidinium]PbI 4 .…”
Section: Introductionmentioning
confidence: 99%
“…PeLEDs have achieved a half-lifetime over 100 hours with DJ-type perovskite materials as emitting layers. 90 Hence, DJ-type perovskite materials is a promising alternative solution to achieving stable PeLEDs.…”
Section: Working Stabilitymentioning
confidence: 99%
“…Organic-inorganic hybrid perovskites have attracted significant interest in solution processed high-performance optoelectronic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Besides the great success in photovoltaics, their unique optical and electrical properties make hybrid perovskites promising candidates for next generation light emitting diodes (LEDs) [19][20][21][22][23][24][25][26]. Many efforts have been made to enhance the luminescence from hybrid perovskites, such as passivating defects [27][28][29][30][31], constructing multiple quantum wells [30], utilizing plasmonic structures [31,32], and so on.…”
Section: Introductionmentioning
confidence: 99%